Dead Reckoning : Dhaka Ki Kahaani Kuch Apni Kuch Ghairon Ki Zubani - Boss, Sermila; Translation : Nazar Hussain Kazmi (Rawalpindi Army Publishing House, 2013)
First Book of the war about the 1971 Pakistan between India.And the memories of warrior of this war. and also describe the detail of war.
Includes Bibliography.
Originally Published in Great Britain in 2011.
Keywords: Interviews -- Collective Memory -- Social Aspects -- War Victims -- War and Society